Analisis Gaya Bahasa Dan Makna Dari Lagu “Amin Paling Serius” Karya Sal Priadi Dan Nadin Amiza - Raden Arla Syamira Putri (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
The song "Amin Paling Serius" popularized by Sal Priadi and Nadin Amizah is a very unique and magical song because the lyrics use a dialogue format between two male and female characters. The song with orchestral strains composed by Lafa Pratomo as the music producer for the song "Amin Paling Serius" brings listeners to explore their deepest feelings of love and hope. “Amin Paling Serius” tells of the love story of two people who come from two different backgrounds, and both offer their prayers with the most serious amen for their love journey together. The lyrics in this song are also very beautiful and poetic, coupled with a figurative language style that makes the song even more alive. The aims of this study include (1) analyzing the use of figurative language in the lyrics of the song "Amin Paling Serius". (2) Understanding and expressing the meaning of the song "Amin Paling Serius". The method used in this research is a qualitative research method. The results of this study are expected to be able to understand the meaning and use of figurative language in the song "Amin Paling Serius" which was popularized by Sal Priadi and Nadin Amizah.